Micro-Scale CPV Performance Enhancement through V-Trough Concentration and Passive Cooling - Robert, Nicholas; Paramasatya, Johanes Dimas; Prastomo, Niki (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2025)
The global reliance on fossil fuels has driven the need for clean, renewable alternatives. Concentrated Photovoltaic (CPV) systems offer a promising solution by increasing energy yield per unit area, particularly in regions with high solar irradiance. This study investigates the performance enhancement of a micro-scale CPV system through the integration of a V-trough optical concentrator and passive thermal regulation mechanisms. Five system variants were developed and tested: a baseline with no enhancement, a standard CPV, and three CPV systems incorporating heat sinks, heat pipes, and a hybrid of both. Optical simulations were performed to achieve a 2× concentration ratio using planar mirrors angled at 60°, while all cooling systems relied on passive methods to maintain simplicity and low cost. Field tests conducted in a tropical environment revealed that all CPV systems outperformed the baseline, with the hybrid-cooled system delivering the highest average power output—138.76 mW, a 32.37% improvement over the baseline. Surface temperatures were also significantly reduced, with the hybrid system lowering temperatures by up to 6.8°C. These results highlight the synergistic potential of combining optical and passive thermal enhancements in compact CPV designs, providing a scalable, cost-effective solar energy solution suitable for rural and off-grid applications in high-irradiance regions.